Pelatihan Daur Ulang Limbah Botol Plastik Pada Remaja Di Indekos Falih Metro - Silvia Fatma Sari; Rina Mida Hayati; Ani Mardiantari; Didik Aji Kusno; Finny Ligery; Miftahur Rohman; Imam Turmudzi; Fredi Irawan; Ahmad Syaifudin Zuhri; Ressi Susanti (Wisanggeni: Jurnal Pengabdian Masyarakat, 2025)
Plastic bottle waste is one of the main contributors to environmental pollution in Indonesia. Metro City, as part of Lampung Province, faces similar challenges in managing plastic waste. Falih Boarding House in Metro Pusat District is a strategic location to conduct plastic bottle waste recycling training, considering the large number of teenagers living there. The purpose of this activity is to improve the knowledge and skills of teenagers in managing plastic waste through the 3R approach.(Reduce, Reuse, Recycle).The methods used include interactive lectures, demonstrations, and hands-on practice in making creative products from used plastic bottles, such as piggy banks and accessories. The expected results of this training are increased environmental awareness among teenagers, reduced volume of plastic waste around boarding houses, and empowerment of teenagers to produce products with economic value from plastic waste. This activity is also expected to be a model for other boarding house communities in Metro City in efforts to manage waste more sustainably.